The Women's Issue in the 21st Century: From the Perspective of Ama Ata Aidoo to the Light of Pain and Suffering (International Journal of Food and Nutritional Sciences, 2022)
A Jewish rabbi used to thank God that he was not born a woman. It was no different in Roman and Greek culture two thousand years ago. Education has liberated women to some extent in those two thousand years. Feminism has helped women to think and live independently of men. But the rapes throughout India in recent years, the broken marriages, and the other social ills raise many questions. Where are women now in the patriarchal world? Where do they need to go now? Are they moving in the right direction? Through the female characters in Ama Ata Aidoo’s novel Changes: A Love Story, this research paper discusses what ails women in the 21st century and how they can solve their problems in a patriarchal world. The existential struggle in the lives of endless educated women in the face of pain and suffering is discussed. Although women's equality and complementarity are real, the social mask and cultural realities in different societies are always against women in a patriarchal world, as we see in the characteristic portrayals of FusenaKondey, Opokuya Dakwa and EsiSekyl, which show the existential struggle of a woman in everyday life. The pain and suffering endured by the women in Aidoo's novel succinctly portrays the subjugation of women throughout the world.